2018
DOI: 10.1542/peds.2017-3737
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Community-Based Intervention and Asthma Outcomes in African American Adolescents

Abstract: A comprehensive family- and community-based treatment significantly improved FEV, medication adherence, asthma symptom frequency, and inpatient hospitalizations in African American adolescents with poorly controlled asthma. Further evaluation in effectiveness and implementation trials is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(51 citation statements)
references
References 43 publications
1
50
0
Order By: Relevance
“…Potential Interventions Reducing exposure to psychosocial stressors and improving response to them are potential targets for intervention. A randomized clinical trial of Multisystemic Therapy-an intensive family and community-based approach-found that the intervention significantly improved lung function, adherence, and control for black adolescents with poorly controlled asthma [141] consistent with other evidence supporting family therapy for health [142]. Early data suggests other interventions to improve coping, such as mindfulness-based stress reduction, may be beneficial [143,144].…”
Section: Psychosocial Stress: Childhood Adversity and Community Violencementioning
confidence: 56%
“…Potential Interventions Reducing exposure to psychosocial stressors and improving response to them are potential targets for intervention. A randomized clinical trial of Multisystemic Therapy-an intensive family and community-based approach-found that the intervention significantly improved lung function, adherence, and control for black adolescents with poorly controlled asthma [141] consistent with other evidence supporting family therapy for health [142]. Early data suggests other interventions to improve coping, such as mindfulness-based stress reduction, may be beneficial [143,144].…”
Section: Psychosocial Stress: Childhood Adversity and Community Violencementioning
confidence: 56%
“…Where AYA are struggling to successfully self‐manage their asthma, psychological interventions using a CBT based or multi‐systemic therapy approach can be recommended to improve asthma knowledge, improve adherence, self‐management and symptom control (Grade B) 39‐42 . This is based on a small number of randomized controlled asthma trials.…”
Section: Transition Specific To Allergic Conditions And/or Asthmamentioning
confidence: 99%
“…Twelve papers reporting on nine studies explored the impact of psychological interventions on adolescents with asthma ( Figure 1). [17][18][19][20][21][22][23][24][25][26][27][28] Eight papers were from the USA, three from Iran and one from Germany. All but two of the studies were randomized controlled trials; Hempel et al 17 employed a nonrandomized controlled design and Hemati et al 18,19 conducted alternate allocation to intervention or control group.…”
Section: Psychological Interventionsmentioning
confidence: 99%
“…Three papers reported findings from a prospective randomized controlled trial using Multisystemic Therapy for African American adolescents with moderately to severe poorly controlled asthma. [25][26][27] This therapy incorporates cognitive behavioural therapy to promote behavioural changes and coping skills, delivered at home over 6 months. Adherence, asthma knowledge, asthma symptoms and hospitalizations were found to significantly improve in the intervention compared with the control group, [25][26][27] with a per protocol analysis showing a medium effect on adherence.…”
Section: Psychological Interventionsmentioning
confidence: 99%